Pengengembangan Laboratorium Bisnis Melalui Segmentasi, Targeting Dan Positioning - Nopianto, Agus; Paningrum, Destina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
Cultivate new entrepreneurs who are well educated and have a mindset to create employment, entrepreneurship is not only defined as business skills. More than that entrepreneurship is being creativeÂ innovative , and pull the trigger. Entrepreneurship can be applied in all areas of work and life, so it is useful as a preparation to the future of the students, if you want a career in any field. Laboratory Business Development aims to become business incubator that accompany the students who are interested in or have previously entrepreneurship.Keywords: Entrepreneurship, Segmenting, Targeting dan Positioning